rút gọn phân số sau: $\frac{x^3+y^3+z^3-3xyz}{(x-y)^2+(y-z)^2+(z-x)^2}$

Question

rút gọn phân số sau:
$\frac{x^3+y^3+z^3-3xyz}{(x-y)^2+(y-z)^2+(z-x)^2}$

in progress 0
Cora 6 ngày 2021-12-04T05:53:46+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-12-04T05:55:19+00:00

    Đáp án:

    \(\dfrac{1}{2}\left(x+y+z\right)\)

    Giải thích các bước giải:

    \(\dfrac{x^3+y^3+z^3-3xyz}{\left(x-y\right)^2+\left(y-z\right)^2+\left(x-z\right)^2}\)

    \(=\dfrac{\left(x+y\right)^3-3x^2y-3xy^2-3xyz+z^3}{x^2-2xy+y^2+y^2-2yz+z^2+x^2-2xz+z^2}\)

    \(=\dfrac{\left[\left(x+y\right)^3+z^3\right]-3xy\left(x+y+z\right)}{2x^2+2y^2+2z^2-2xy-2yz-2xz}\)

    \(=\dfrac{\left(x+y+z\right)\left[\left(x+y\right)^2-z\left(x+y\right)+z^2\right]-3xy\left(x+y+z\right)}{2\left(x^2+y^2+z^2-xy-yz-xz\right)}\)

    \(=\dfrac{\left(x+y+z\right)\left(x^2+2xy+z^2-xz-yz+z^2-3xy\right)}{2\left(x^2+y^2+z^2-xy-yz-xz\right)}\)

    \(=\dfrac{\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-xz\right)}{2\left(x^2+y^2+z^2-xy-yz-xz\right)}\)

    \(=\dfrac{x+y+z}{2}\)

    \(=\dfrac{1}{2}\left(x+y+z\right)\)

    0
    2021-12-04T05:55:26+00:00

    Xét tử số:

    $x^3+y^3+z^3-3xyz$

    $=x^3+3x^2+3xy^2+y^3+z^3-3xyz-3x^2y-3xy^2$

    $=(x^3+3x^2y+3xy^2+y^3)+z^3-(3xyz+3x^2y+3xy^2)$

    $=(x+y)^3+z^3-3xy(z+x+y)$

    $=(x+y+z)[(x-y)^2-z(x+y)+z^2]-3xy(x+y+z)$

    $=(x+y+z)(x^2+2xy+y^2-xz-yz+z^2-3xy)$

    $=(x+y+z)(x^2+y^2+z^2-xy-yz-xz)$

    Xét mẫu số:

    $(x-y)^2+(y-z)^2+(z-x)^2$

    $=x^2-2xy+y^2+y^2-2yz+z^2+z^2-2xz+x^2$

    $=2x^2+2y^2+2z^2-2xy-2xz-2yz$

    $=2(x^2+y^2+z^2-xy-yz-xz)$

    Vậy: `\frac{x^3+y^3+z^2-3xyz}{(x-y)^2+(y-z)^2+(z-x)^2}=\frac{(x+y+z)(x^2+y^2+z^2-xy-yz-xz)}{2(x^2+y^2+z^2-xy-yz-xz)}=(x+y+z)/2`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )